DEVELOPMENT OF THE PATIENT CARE MODEL FOR CEREBROVASCULAR DISEASE IN PAK-CHOM HOSPITAL, LOEI PROVINCE - Sirakan, Arunee; Thitithirarot, Thunyapat; Piakhuanon, Piyawan (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
This study aimed to develop a care model for stroke patients at Pak Chom Hospital, Loei Province, using research and development approach. The study was divided into four phases: 1) situation analysis, 2) care model development, 3) implementation of the developed model, and 4) outcome evaluation. The sample consisted of 34 healthcare personnel involved in caring for stroke patients. The research instrument was a questionnaire assessing satisfaction with the developed stroke care model. The results revealed that the developed model comprised six components: 1) personnel, 2) ambulance, 3) tools and equipment, 4) data recording, 5) information system development, and 6) quality review and monitoring. After implementing the model, there were no cases of ventilator-associated pneumonia and mortality. The average time from admission to referral decreased to 98 minutes. The access rate to Stroke Fast Track treatment was 42.85%, and the rate of receiving rt-PA was 29.03%. The personnel’s satisfaction was at a high level (x̄ = 4.85, SD = 0.37).The findings suggest that the developed stroke care model is effective in improving the quality of patient care and can be applied in other community hospitals. However, further studies are needed to identify ways to increase access to treatment and thrombolytic therapy, as well as to promote public knowledge and awareness of stroke warning signs.